Dwelling in marble halls: a relevance-theoretic approach to intertextuality in translation - Almazán García, Eva María (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2001)
In this article we explore the possibility of using a relevance-theoretic approach for translating intertextual references in a literary context. On the basis of an example taken from L.M. Montgomery's Anne of Green Gables, we propose an interpretation of the original text based on concepts taken from Relevance Theory (henceforth RT) as designed by Sperber and Wilson (1986) and developed by Blakemore (1992). Gutt's contribution (1991), viewed as an insightful but still preliminary step towards an application of RT to the theory and practice of translation, is then made to crystalize in valid criteria which may orient the translator in the decision-making process.